Need of premarital care - Bansiwal, Reeta; Mittal, Pratima; Jyotsna, .; Sharma, Yogita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Marriage is considered a remarkable event in an individual’s life. It provides people with a sense of belonging, support, security and responsibility. We put so much of efforts to find a good match for our younger and loved ones but we forget to match the most important wealth of our life “Health”. This study aimed to know the knowledge, attitude and practice of the population through a structured questionnaire. Methods: A cross-sectional study was conducted using a self-administered questionnaire which was distributed to 110 males and 110 females attending Medicine and Gynae OPD at Safdarjung hospital, New Delhi. Participants were questioned according to the self administered questionnaire and their answers were evaluated. Results: Only 11% of males new of premarital counseling and none of the females were aware of premarital care. Contraception knowledge was also poor among females as 7% females new only I-Pill as the method of contraception. After knowing the importance of premarital counseling and screening 92% males and 52 % females agreed for premarital counseling and screening. Conclusions: Marriage provides people with a sense of belonging, support, security and responsibility. Premarital care nurtures it and fill its “Neev” with the goodness of health. Therefore, it is recommended that premarital care is important before every marriage for the happy and healthy family ahead.